Differences in Clinical and Laboratory Features of Pregnant and Non-Pregnant Female with Hospitalized COVID-19 - Muhana F. Ilyas; Revi G. H. Novika; Winastari Y. Triniputri; I M. E. W. Pradipta; Ni W. P. S. Ksamawati; Nurul J. Wahidah; Hartono Hartono; Lanjar Sumarno (Iranian Journal of Nursing and Midwifery Research)
Background: The impact of COVID-19 on vulnerable populations, including pregnant female, is critical due to higher risks and potential complications. This study aims to compare the clinical and laboratory features of COVID-19 between pregnant and non-pregnant female. Materials and Methods: This retrospective cohort study included 245 COVID-19 patients admitted to Universitas Sabellas Maret (UNS) Hospital, Indonesia, from March 2020 to May 2022. Among them, 72 were pregnant, and 173 were non-pregnant. Data on demographics, clinical presentations, and laboratory findings were collected from medical records. Statistical analysis utilized Chi-square or Fisher exact tests, Mann-Whitney or independent t-tests, and multiple linear regression. Results: No significant demographic differences were found, except in hospitalization status. Clinically, pregnant female had a higher prevalence of symptoms such as cough (p = 0.002), fatigue (p = 0.025), and shortness of breath (p = 0.035), with no differences in other symptoms or length of stay. Laboratory findings indicated significant differences in White Cell Count (WCC), Absolute Lymphocyte Count (ALC), High Fluorescence Lymphocyte Count (HFLC), lymphocyte percentage, neutrophil percentage, Neutrophil Lymphocyte Ratio (NLR), Red Cell Count (RCC), Hemoglobin (Hb), Hematocrit (Hct), Platelet Count (PC), Prothrombin Time (PT), International Normalized Ratio (INR), D-Dimer, and Sodium (p values < 0.05). Multivariate analysis identified WCC, lymphocyte percentage, HFLC, neutrophil percentage, PT, INR, D-Dimer, Creatinine, and Potassium as significant predictors of length of stay (R²adj = 0.874, F = 17.979, p < 0.001). Conclusions: Pregnant female with COVID-19 exhibited distinct laboratory profiles compared to non-pregnant female. These findings highlight the need for tailored management strategies for COVID-19 in pregnant patients and provide a foundation for further research.